Design and production of new type reinforced U-profile composite panels - Uslu, Merve; Kaman, Mete Onur; Yanen, Cenk; Albayrak, Mustafa; Dağ, Serkan; Erdem, Serkan; Turan, Kadir (Toros Üniversitesi, 2024)
In aircraft design, factors such as fuel efficiency, lightness and durability are critical due to the effect of various loads. Therefore, the use of "U" profile beams, which are stronger in terms of strength, provides versatile advantages. In this study, a reinforced composite panel was designed and fabricated by adding support beams to the "U" profiles to maintain the safety and integrity of aircraft structures. Glass fiber and epoxy resin were employed in the composite production process. The vacuum infusion method was employed for composite production, with molds specifically designed for the "U" profile and "I" support beams. Following production, the compatibility of the "U" profile, "I" support beam and sub-composite base forming the composite panel was evaluated. It was determined that the produced "I" support beam constituted only 18.8% by weight of the composite panel.
Keywords: Solid Mechanics; Katı Mekanik; Material Design and Behaviors; Malzeme Tasarım ve Davranışları